Cable-stayed bridges : 40 years of experience worldwide - Svensson, Holger (Ernst & Sohn, 2012)
The need for large-scale bridges is constantly growing due to the enormous infrastructure development around the world. Since the 1970s many of them have been cable-stayed bridges. In 1975 the largest span length was 404 m, in 1995 it increased to 856 m, and today it is 1088 m. Thus the economically efficient range of cable-stayed bridges is tending to move towards even larger spans, and cable-stayed bridges are increasingly the focus of interest worldwide. This book describes the fundamentals of design analysis, fabrication and construction, in which the author refers to 250 built examples.